Cognitive dissonance in the psychology of managers professional speech - VlasenkoОlena; Korolchuk, Valentyna; Myronets, Serhii; Boltivets, Sergii; Mykhaylyshyn, Ulyana (Interacción y Perspectiva, 2023)
The article determines that one of the main skills of becoming a manager as a specialist is the mastery of professional speech. It ensures the development of cooperation and mutual understanding between colleagues, partners, managers and subordinates. Professional speech is a mandatory tool for a manager when managing workers and establishing business relationships. Professional speech determines the use of professional terms that correspond to the specifics of managerial activity and the particularities of the management industry. It discovered the relationship between the degree of the use of professional terms in communication and the level of management to which the respondent belongs. One revealed a dissonance between the use of professional terms and their perception. The analysis showed that the lower the level of management, the more negatively managers perceive professional terms in professional speech. At the same time, the level of the use of professional terms is very high in all groups of managers. One subject revealed dissatisfaction with the level of professional speech skills acquired at higher education institutions. Therefore, future managers should master professional speech skills at a higher education institution.